2009
DOI: 10.1016/j.jtcvs.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of postinfarction ventricular septal rupture: Risk factors of early and late death

Abstract: Early outcome after repair of ventricular septal rupture improved significantly during time, with 30-day mortality being 21% in the last decade. Five- and 10-year cumulative survival was 50% and 32%, respectively. Shock at surgical intervention and incomplete coronary revascularization were strong and independent predictors of poor early and late survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 33 publications
4
55
0
1
Order By: Relevance
“…Prolonged CPB time was found to be a risk factor of overall mortality in several previous studies [5,6]. However, prolonged CPB time was not a predictor of cumulative mortality in 30-day survivors in the cited study [6], and the authors suggested that the prolonged CPB might have been confounded by underlying factors.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Prolonged CPB time was found to be a risk factor of overall mortality in several previous studies [5,6]. However, prolonged CPB time was not a predictor of cumulative mortality in 30-day survivors in the cited study [6], and the authors suggested that the prolonged CPB might have been confounded by underlying factors.…”
Section: Discussionmentioning
confidence: 92%
“…Although a recent report demonstrated a significant improvement of surgical outcomes in the second half of the 25-year study period [6], there were no remarkable changes in the surgical outcomes of post-infarct VSD in the other previous studies [1-5,7-18]. The dismal outcomes may be attributable to the disease nature of post-infarct VSD: the surgical outcomes of post-infarct VSD are predominantly affected by the preoperative patients' hemodynamic stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Th e ideal timing of VSD repair is a point for debate ( Table 1 ) ( 2,5,9,(12)(13)(14). A few studies support our current strategy of delaying surgery, allowing optimization of medical management prior to intervention if permissible.…”
Section: Discussionmentioning
confidence: 99%